O Programa Nacional de Melhoria de Acesso e da Qualidade da Atenção Básica (PMAQ-AB): Gestão do Trabalho e Repercussões na Saúde dos Servidores de um Município Da Região Metropolitana De São Paulo – SP - Vechia Leiva, Patrícia Rosin Lacintra [UNIFESP] (2019)
One of the challenges for the SUS’s strengthening and the actions fragmentation overcoming is related to necessity of health professional’s valorization. To the Health Ministry, improving the quality of services in primary attention care through PMAQ-AB can be a way to overcome this fragmentation. This research is about the primary attention care workers' view on this issue. The objective was to analyze the changes in the conditions and organization of work with the implementation of PMAQ-AB, from the perspective of work management, in Guarulhos, the second largest city in the state of São Paulo. Of qualitative character, through a case study, realized a bibliographic review was; official documents analysis that generated with the contracting process of PMAQ-AB; semistructured interviews with service and central level managers, focus groups with contract workers and participant observation during three-month period in 2016. By analyzing the data collected, the Content Analysis approach used. We could observe that the Program did not mean an improvement in the processes of work in the AB, nor in the working conditions in the city of Guarulhos, especially in what concerns the infrastructure and staff. In addition, it affected the health of the servers with intense wear, stress, hard work and the lack of legal devices that effectively take care of health, especially of their mental health.